2020
DOI: 10.1063/1.5130149
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the nearly perfect and wavelength-adjustable absorption of MoS2 monolayer using defective quasi photonic crystals

Abstract: In recent years, two-dimensional materials such as MoS2 monolayers have attracted a lot of attention due to their high absorption. This study proposes the use of MoS2 monolayers as part of the defect in Fibonacci and Thue-Morse defective quasiphotonic crystals (DQPCs) to create an adjustable defect mode with relatively high absorption. The wavelength adjustability of the defect mode is investigated by parameters such as generation number, periodicity, and type of sequence used in DQPCs. The results revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The latter has also been observed in the TIR configuration. , The high oscillator strength and intrinsic losses of excitons in transition metal dichalcogenides (TMDs) enhance light–matter interactions . Therefore, several studies have focused on enhancing TMDs absorption using various fabrication strategies, reaching nearly perfect absorption even in monolayers. Importantly, the same excitonic characteristics make TMDs great candidates also for strong light–matter coupling.…”
Section: Introductionmentioning
confidence: 99%
“…The latter has also been observed in the TIR configuration. , The high oscillator strength and intrinsic losses of excitons in transition metal dichalcogenides (TMDs) enhance light–matter interactions . Therefore, several studies have focused on enhancing TMDs absorption using various fabrication strategies, reaching nearly perfect absorption even in monolayers. Importantly, the same excitonic characteristics make TMDs great candidates also for strong light–matter coupling.…”
Section: Introductionmentioning
confidence: 99%
“…The diameter of the tetramerized Ag nanorods is indicated as d i (i = 1,2,3,4), and their height are denoted as h. The refractive index of the SiO 2 spacer is 1.45, and its thickness is t. The dielectric constant of Ag are take from Johnson and Christy [27]. The thickness of monolayer MoS 2 is set as 0.615 nm, and its wavelength-dependent complex permittivity is determined by the Lorentz model [28,29]:…”
Section: Structure and Methodsmentioning
confidence: 99%
“…It is well known that an absorber is highly desired for many applications such as photodetectors, solar cells, and thermal management [19][20][21][22][23]. Recently, monolayer MoS 2 has been utilized to realize high absorption in visible frequency range [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. However, determined by the ultrathin thickness of monolayer MoS 2 , the light absorption efficiency of monolayer MoS 2 is low (exhibiting absorption only about 10% in the wavelength region above its band-gap at normal incident light) [37], which limits its progress towards many practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…N. Ansari et al studied 1D photonic crystal including periodic dielectric layers with monolayer MoS 2 constituent layers and alternative layers order and found that such a structure can increase optical absorption [28]. Photonic quasicrystals with monolayer MoS 2 , such as Fibonacci, Thue-Morse and Octonacci ordered artificial sequences, have been chosen to fabricate new types of broadband absorber in the visible frequency range because of their unique band structure [24,25,30]. Also, efforts have been made on absorbers with multi-band absorption peaks due to their important role in multi-spectral detection, sensing, optical communication, and electro-optical systems.…”
Section: Introductionmentioning
confidence: 99%